Incompatible Heroes That Turn The Facts Upside Down - Kocak, Aynur; Ugurcan, Fatma Zehra (GELENEKSEL YAYINCILIK LTD STL, 2021)
Clowns attacking social norms by appearing in carnivals in the Middle Age have an important function such as reversing reality. Clowns get strength from their irregularity when attacking reality. Because irregularity is perceived as a more acceptable situation by the society, especially if it is exhibited under the appearance of insanity, purity and stupidity. The most important feature of these types behind the curtain of irregularity is that they lead to a cynical laugh. Literature researchers have generally focused on why these types make us laugh but have not been very interested in what kind of results these types make us laugh or what is the purpose of using these types. People see absurd types as a symbol of incompatibility, and even these have been frequently used in literature. There is undoubtedly a reason why absurd types emerging with stupid, insane, pure, bad-looking human manifestations are so popular. To find this purpose, it is necessary to get support from phenomenological theory. There is a mystery that suggests the truth in the use of stupidity and madness. The phenomenological approach focuses on the relativity of reality. Reality is like a slick and floating mass; it is difficult to make sure if an object matches its known counterpart. From a phenomenological point of view, the use of maladaptive behaviors such as stupidity in literature serves the purpose of playing with meanings. So, it can be said that the hero who takes the appearance of a fool, crazy or beggar in disguise also has a plan that can change reality. Such heroes are hidden behind a negative picture, such as stupidity, madness, and dirty looks in the epics, but eventually always turn this picture down into victorious heroes. This transformation of the hero benefits the reader and the audience to think about the truth. What is the truth? Is stupid really stupid or is he a stupid looking smart? So is smart really smart? Why does stupid try to achieve the results he wants to achieve by using his incompatible character? All of these appear as riddles in epics. The person who will solve the riddle using the clues given in the epics is the listener and reader. In this study, the Greek epic Odysseia, Kam Bure Bey Oglu Bamsi Beyrek from Dede Korkut, The Bey Boyrek Story, which is similar to this one, Alip Manas, Er Samir and Kozuyke epics of Altai Turks and Alpamus epic from Uzbek Turks will be examined. Based on these epics, the commonality in the methods of resolving the negative events that happened to the heroes will be emphasized, state of incompatibility, which the heroes use as a method in the episode of hero's return, which is a widely known topic in the field of folklore, will be examined and its function in the narrative will be evaluated with a phenomenological approach.
Keywords: Irregularity; fool; stupid; madmen; epic; phenomenological approach; Arts & Humanities - Other Topics